2010
DOI: 10.4049/jimmunol.1002154
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ripA Alleviates Suppression of the Inflammasome and MAPK by Francisella tularensis

Abstract: Francisella tularensis is a facultative intracellular pathogen and potential biothreat agent. Evasion of the immune response contributes to the extraordinary virulence of this organism although the mechanism is unclear. Whereas wild-type strains induced low levels of cytokines, an F. tularensis ripA deletion mutant (LVSΔripA) provoked significant release of IL-1β, IL-18, and TNF-α by resting macrophages. IL-1β and IL-18 secretion was dependent on inflammasome components pyrin-caspase recruitment domain/apoptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
66
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 55 publications
(85 reference statements)
5
66
1
Order By: Relevance
“…However, as reported in previous studies, we did not observe this NLRP3 dependence at 24 h post-infection either in F. tularensis LVS or the FTL_0325 mutant-infected macrophages. Similar to several previous reports, our results also demonstrate an AIM2-dependent but NLRP3-independent inflammasome activation at 16 -24 h post-infection in F. tularensis LVS-infected macrophages (34,35,48).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, as reported in previous studies, we did not observe this NLRP3 dependence at 24 h post-infection either in F. tularensis LVS or the FTL_0325 mutant-infected macrophages. Similar to several previous reports, our results also demonstrate an AIM2-dependent but NLRP3-independent inflammasome activation at 16 -24 h post-infection in F. tularensis LVS-infected macrophages (34,35,48).…”
Section: Discussionsupporting
confidence: 80%
“…A phenotype similar to the FTL_0325 has also been reported for the ⌬ripA and mviN mutant of F. tularensis LVS. RipA suppresses the MAPK signaling pathway to down-regulate proIL-1␤ synthesis and IL-1␤ production and that activation of IL-1␤ in ⌬ripA mutant is mediated by an AIM2-dependent inflammasome (34). However, Peng et al (36) reported that the hyperinflammatory and hypercytotoxic nature of the ⌬ripA mutant was due to altered membrane integrity and intramacrophage lysis of the mutant, resulting in the release of excessive bacterial DNA and activation of AIM2 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yersinia, Shigella, and Bacillus anthracis inhibit MAPK signaling to suppress inflammatory response that permits bacterial growth and dissemination (55)(56)(57)(58). It has been reported that F. tularensis LVS suppresses MAPK signaling via intracellular growth locus C and RipA (16,19). This study reports that the FTL_0325/FTT0831c proteins of both the F. tularensis LVS and SchuS4 suppress proinflammatory cytokine response by inhibiting NF-B signaling.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, it has been demonstrated that FopC suppresses IFN-␥ signaling and thus interferes with generation of an effective innate immune response (59). Several other structural components of both the LVS and F. novicida such as MviN, a lipid II filppase (61), RipA, a cytoplasmic membrane protein (19), or the LPS O-antigen (62) and capsular components have been shown to be required for virulence, suppression of proinflammatory cytokines, and cell death in infected macrophages. Results from the present study indicate that FTL_0325 serves to play a role different than these structural proteins.…”
Section: Discussionmentioning
confidence: 99%